EFEKTIFITAS MODIFIKASI PERILAKU UNTUK MENGATASI ENURESIS PADA ANAK - Evi Syafrida Nasution (Fakultas Psikologi Universitas Borobudur, 2018)
This study aims to test the effectiveness of the behavior modification program to reduce the behavior of bedwetting (enuresis) during sleep at night with the method of extinction and token economy. This study used single case experiment method with multiple baseline design, so that the effect of the therapy that has been given can be evaluated well. The data collection methods used in this study are interviews, observation, and psychological examination. Subjects in this study amounted to one person, aged 8 years and 9 months, and experienced enuresis. The results of this study indicate that behavior modification program with extinction method and giving token economy to reduce the behavior of bedwetting subject while sleeping at night can be said successful. The change in frequency of bed wetting has decreased significantly. Although until now the subject is sometimes still wet one time in one night. This is because parents are difficult to limit the subject of playing with their friends outside the house like playing romp and less assertive in the application of rules at home. Changes in the behavior of bedwetting a good enough subject is not independent of the role of parents who are willing to assist researchers in applying the rules of implementation of this behavior modification at home. Keywords: extinction, behavior modification, token economy